2019
DOI: 10.1038/s41419-019-2010-6
|View full text |Cite
|
Sign up to set email alerts
|

ADP secreted by dying melanoma cells mediates chemotaxis and chemokine secretion of macrophages via the purinergic receptor P2Y12

Abstract: Melanoma immunotherapy is still not satisfactory due to immunosuppressive cell populations within the tumor stroma. Targeting tumor-associated macrophages (TAM) can help to restore an anti-tumor immunity. Previously, we could show that classical TAM markers expressed in vivo need a 7 day M-CSF/dexamethasone/IL-4 (MDI) stimulation for their induction in peripheral blood monocytes (pBM) in vitro. To identify possible novel therapeutic targets on TAM, gene expression analysis of MDI-treated pBM was performed. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…It has been well-established in literature that the levels of ATP increase in the tumor microenvironment ( Idzko et al, 2014 ; Di Virgilio et al, 2018 ). This is especially true in the case of cancers that are therapeutically targeted wherein death of drug- or radiation-sensitive cells results in changing the contents of the microenvironment, of which ATP, among others, is a prominent molecule ( Martins et al, 2009 ; Schneider et al, 2015 ; Kloss et al, 2019 ). We observed that the treatment with doxorubicin also showed an increase in the levels of eATP in the media 48 h post-stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well-established in literature that the levels of ATP increase in the tumor microenvironment ( Idzko et al, 2014 ; Di Virgilio et al, 2018 ). This is especially true in the case of cancers that are therapeutically targeted wherein death of drug- or radiation-sensitive cells results in changing the contents of the microenvironment, of which ATP, among others, is a prominent molecule ( Martins et al, 2009 ; Schneider et al, 2015 ; Kloss et al, 2019 ). We observed that the treatment with doxorubicin also showed an increase in the levels of eATP in the media 48 h post-stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…33 The purinergic G-protein coupled receptor P2RY12 is a therapeutic target of the clinically approved anti-thrombotic drugs cangrelor and clopidogrel. 34 Kloss et al 34 demonstrated that P2RY12 activation triggers the migration of macrophages to necrotic tumor areas and modulates chemotaxis and the chemokine secretion of macrophages. Our research revealed that the genes for all four of these proteins (P2RY12, GP6, GP9, and GP1BA) were upregulated in PD samples in the GSE49126 and GSE100054 datasets, although only GP1BA and GP6 were upregulated in our clinical cohort of PD patients.…”
Section: Discussionmentioning
confidence: 99%
“… 33 The purinergic G-protein coupled receptor P2RY12 is a therapeutic target of the clinically approved anti-thrombotic drugs cangrelor and clopidogrel. 34 Kloss et al. 34 demonstrated that P2RY12 activation triggers the migration of macrophages to necrotic tumor areas and modulates chemotaxis and the chemokine secretion of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…P2Y 12 receptor protein expression has also been verified. Such macrophages display a phenotype similar to that of tumor-associated macrophages (TAM) [ 110 ]. In the same work, P2Y 12 expression was confirmed on CD163-expressing TAM of melanoma in situ.…”
Section: P2y 12 Receptormentioning
confidence: 99%
“…Pharmacological inhibition of P2Y 12 receptor was found to evoke an endoplasmic reticulum (ER) stress response that appears to block M2 markers such as arginase-1, indicative of a shift towards M1 [ 109 ]. Similar to the P2Y 2 receptor on macrophages, which senses ATP and UTP released from apoptotic cells [ 55 ], the P2Y 12 receptor has been reported to direct migration of TAM towards ADP-releasing melanoma cells in necrotic tumor areas [ 110 ]. In recombinant U937 cells, stimulation of ectopic P2Y 12 receptor with ADP induced the secretion of chemokines including CXCL8 [ 110 ].…”
Section: P2y 12 Receptormentioning
confidence: 99%